2016
DOI: 10.1155/2016/4396756
|View full text |Cite
|
Sign up to set email alerts
|

Collagen V Is a Potential Substrate for Clostridial Collagenase G in Pancreatic Islet Isolation

Abstract: The clostridial collagenases, H and G, play key roles in pancreatic islet isolation. Collagenases digest the peptide bond between Yaa and the subsequent Gly in Gly-Xaa-Yaa repeats. To fully understand the pancreatic islet isolation process, identification of the collagenase substrates in the tissue is very important. Although collagen types I and III were reported as possible substrates for collagenase H, the substrate for collagenase G remains unknown. In this study, collagen type V was focused upon as the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Several studies have also shown detrimental effects of enzymatic islet isolation on peripheral islet ECM, such as on collagens [ 2 , 6 ] and laminins [ 119 ]. Collagenases digest several collagen types, such as types I, III, IV and V [ 25 ]. This has a dramatic impact on cell viability [ 27 ].…”
Section: Considerations For Engineering and Future Applications Of Ecmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also shown detrimental effects of enzymatic islet isolation on peripheral islet ECM, such as on collagens [ 2 , 6 ] and laminins [ 119 ]. Collagenases digest several collagen types, such as types I, III, IV and V [ 25 ]. This has a dramatic impact on cell viability [ 27 ].…”
Section: Considerations For Engineering and Future Applications Of Ecmentioning
confidence: 99%
“…Although selective, the process of enzymatic degradation of exocrine connections is not specific [ 2 ] and, as a consequence, many ECM components that surround the islets and interconnect endocrine cells are also damaged [ 2 , 22 ], affecting islet function [ 6 , 21 , 23 , 24 ]. After isolation using ECM-degrading collagenases, the whole microvasculature of the islet is destroyed [ 25 ] and islet cells undergo cell-death processes, such as anoikis, necroptosis and necrosis [ 2 , 22 , 26 , 27 ]. To amplify matters, these processes are associated with the release of highly inflammatory danger-associated molecular patterns (DAMPs) that contribute to immune responses against pancreatic islets [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is particularly remarkable since collagen-VI is resistant toward the activity of bacterial collagenases [136,137], suggesting a distinct protective morphological wall during enzyme-mediated pancreas digestion. Moreover, collagen-V, the second most strongly expressed collagen subtype in the human peri-islet basement membrane, can be degraded by CC-I, but not by CC-II [138]. This finding is in clear contradiction to the proposition that CC-II is the most relevant isoform for islet release when compared with CC-I [47,59].…”
Section: Extracellular Matrix Degradationmentioning
confidence: 65%
“…1 ). Collagenase is also used in islet isolation from human pancreas for transplantation surgery of type 1 diabetes [24] , [37] , [38] , [39] , [40] , [41] , [42] , [43] . It was recently reported that proteases with trypsin-like activity strongly influence islet isolation from the human pancreas [23] .…”
Section: Discussionmentioning
confidence: 99%